1986
DOI: 10.1111/j.1752-1688.1986.tb01880.x
|View full text |Cite
|
Sign up to set email alerts
|

COMPARISON OF FOUR ARTIFICIAL SUBSTRATES AND THE PONAR GRAB FOR BENTHIC INVERTEBRATE COLLECTION1

Abstract: Four different bottom‐placed artificial substrates were compared with the Ponar grab for collecting benthic invertebrates. Artificial substrate samples of organisms were larger and more diverse than those of the grab. Barbeque Basket samplers caught the most taxa and individuals and Beak Trays caught the least. Chironomids and crustaceans were dominant in artificial substrate samples. Exposure habitat (left or right bank) determined taxa availability, whereas sampler design determined suitability for colonizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Thus, they facilitate comparison of environmental effects along watercourses where the macrohabitat is not constant. Slack et al (1986) concluded that artificial substrates can also dramatically reduce the sampling efforts necessary to produce given, precise results. In our case, we were able to establish significant salinity gradient results after sampling only two artificial substrates at each site on each date, as compared to the 335 Surber samples required.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, they facilitate comparison of environmental effects along watercourses where the macrohabitat is not constant. Slack et al (1986) concluded that artificial substrates can also dramatically reduce the sampling efforts necessary to produce given, precise results. In our case, we were able to establish significant salinity gradient results after sampling only two artificial substrates at each site on each date, as compared to the 335 Surber samples required.…”
Section: Discussionmentioning
confidence: 97%
“…However, to assess water pollution, exact duplication of natural conditions is less important than the ability to obtain replicate samples at different times and different locations (Beak et al, 1973;Slack et al, 1986). Substrates consisted of baskets 30.5 cm by 30.5 cm by 15.2 cm made of 1.6-cm mesh wire cloth filled with 7.6 to 15.2-cm diameter cleaned river rock.…”
Section: Methodsmentioning
confidence: 99%
“…For example, orientation is not included in a review of features involved in artificial substrate replication (Rosenberg and Resh, 1982). Some investigators hold the plates rigidly horizontal by mounting the samplers on a bar attached to a stake driven into the riverbed (Arthur and Horning, 1969), on basal plates (Mathers and Martin, 1969;Slack, et aL, 1986), on bricks (Parsons and Tatum, 1974;Cover and Harrel, 1978). or by driving the axial rod into the substratum (Meier, Penrose, and Polak, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators have suspended samplers from nonrigid wires or cords (Hester and Dendy, 1962;Fuilner, 1971;Wefring and Teed, 1980). Artificial substrates for collecting riverine benthic invertebrates may be placed on the riverbed (Beak, et aL, 1973; Gale and Thompson, 1974;Slack, et aL, 1986) or suspended in the water column (Mason, et aL, 1967;Anderson and Mason, 1968;Arthur and Horning, 1969;Fuilner, 1971;Mason, et al, 1973). Mason, et aL (1973), reported that bottom-placed limestone-filled baskets accumulate more sediment and generally are more variable within pairs than are baskets exposed near the water surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation